Evaluating Xanthomonas oryzae pv. oryzae (Xoo) infection dynamics in rice for distribution routes and environmental reservoirs by molecular approaches - Onchira Ritbamrung; Phithak Inthima; Kumrop Ratanasut; Kawee Sujipuli; Tepsuda Rungrat; Kittisak Buddhachat (Scientific Reports)
Abstract Xanthomonas oryzae pv. oryzae (Xoo) is a bacterial pathogen responsible for bacterial leaf blight (BLB) in rice, which can result in significant yield losses of up to 70%. A study evaluated the spread of Xoo in rice fields using environmental samples and employed colorimetric loop-mediated amplification (cLAMP) and PCR for detection. Quantitative PCR (qPCR) was used to measure infection levels. The research compared infection severity between a susceptible rice variety, Phitsanulok 2 (PSL2), and a resistant variety, PSL2-Xa21. Results showed that Xoo infection decreased from the leaves to the roots, but the bacteria persisted in soil and water for up to 12 and 6 weeks, respectively. The cLAMP assay, with the LpXoo4009 primer, effectively detected Xoo at low concentrations in both soil and water. Additionally, common grasses found in rice fields, such as Eriochloa procera, Echinochloa crus-galli and Chloris barbata were identified as temporary reservoirs for Xoo, facilitating its spread. The Xoo pathogen is distributed from infected leaves to roots and then from roots to the soil and nearby water. Grasses in the fields contribute to the perpetuation of the infection cycle serving as potential reservoirs that maintain the pathogen’s presence in the environment.